Az idegen nyelvi tehetség és az érzelmi intelligencia összefonódása - Dakhlaouiné Nagy Judit (2020)
ABSTRACT Judit Dakhlaouiné Nagy, Ágnes Acsainé Dávid Title: The correlation between foreign language aptitude and emotional intelligence Today there is a growing acknowledgement that the emotional acceptance is a key factor, which has a remarkable impact on our life and the chances of success in any area of endeavour. This is probably even more so in the domain of the foreign language equisition. The study was to examine the role of the emotional intelligence in language learning and its impact on a talent for foreign languages. Based on my teaching experience, I went off of the hypothesis that there must be a certain relationship between the two. A total of 55 people participated in the study, of which there were 17 secondary students talented in foreign languages and chosen from different language groups, their parents (34) and their form teachers (4). First, the students were asked to complete a list of quiries related to the most important features of the emotional intelligence such as self-respect, respect towards the others, self- awarenesss and awareness towards the others. The collected data unambiguously showed a very high level of emotional quotient (EQ). Next, the parents were put questions in connection with their children’s plenteous childhood, their opinion of their children’s foreign language talent, what they thought how their children could be motivated, and what their relationship with their children in the family was like. All the parents’ responses have referred to a positive, balanced and supportive family background, which proved to be a great role at shaping their children’s attitude towards learning in general as well as remarkable insightful implications regarding quality language learning not to mention better educational outcomes. Eventually, a test, a list of personal traits to invent a talent was carried out by the form teachers, according to which the perception of emotion has been found to be the strongest predictor of a cognitive and behavioral personality as well as an affective component of foreign language learning. Manapság egyre inkább elismert az tény, hogy az érzelmi elfogadás kulcsfontosságú szerepet játszik az életben, bármilyen emberi tevékenység sikerének lehet a záloga. Ez a megállapítás talán még helytállóbb az idegen nyelvek elsajátításában. A tanulmány az érzelmi intelligencia szerepét vizsgálta az idegen nyelv tanulásában és annak hatását az idegen nyelvi tehetséggel összefüggésben. Abból a feltételezésből indultam ki, hogy léteznie kell valamilyen kapcsolatnak az idegen nyelvi tehetség és a magas érzelmi intelligencia között. 55 ember vett részt a vizsgálatban, 17 idegen nyelvi tehetség, 34 szülő és 4 osztályfőnök. A középiskolás idegen nyelvi tehetségek egy kérdőívet töltöttek ki az érzelmi intelligencia alapvető ismérveivel összefüggésben, mint például az önbecsülés, mások tisztelete, én-tudat, mások iránti tudatosság. Az összegyűjtött eredmények egyértelműen bizonyították a magas érzelmi intelligencia szintjét. Majd a szülői kérdőív megerősítette, hogy ezeknek a gyerekeknek érzelemgazdag gyermekkoruk volt, pozitív, kiegyensúlyozott és támogató családi háttérrel rendelkeztek. Végül, az osztályfőnökök egy a tehetségre vonatkozó általános tulajdonságlistát töltöttek ki, amely alapján levonható volt az a következtetés, hogy az idegen nyelvi tehetségek épp olyan erős kognitív képességekkel, mint amilyen kiemelkedően magas érzelmi intelligenciával rendelkeznek.